The one-dimensional organic inorganic hybrid compound poly[(diethylenetriamine)tetra-μ-iodido-dilead(II)] - Samet Kallel, E. (International Union of Crystallography, 2008)
A new organic–inorganic hybrid, [Pb(2)I(4)(C(4)H(13)N(3))](n), was obtained by the reaction of C(4)N(3)H(10) and PbI(2) at room temperature. The structure is a three-dimensional polymer resulting from the association of PbI(6) octahedra and a mixed lead organic–inorganic PbI(4)(C(4)N(3)H(13)) coordination polyhedron. Both Pb atoms, two I atoms and one N atom lie on a mirror plane. N—H⋯I hydrogen bonds further connect the organic unit and some I atoms.